In vitro antimycotic activity of chemical constituents from Dipterocarpus verrucosus, Dipterocarpus cornutus and Diptericarpus crinitus against opportunistic filamentour fungi - Wan Mohd Zain, Wan Zuraida; Ahmat, Norizan; Rukayadi, Yaya; Osman, Che Puteh; Yusoff, Nor Asma Husna; Winda, Neneng (Life Sciences Society of Pakistan, 2019)
This paper will discuss, in vitro investigation of chemical constituents extracted from the stem bark of Dipterocarpus verrucosus, Dipterocarpus crinitus and Dipterocarpus cornutus against opportunistic filamentous fungi. In this research, 17 compounds comprised of twelve oligostilbenoids, (-)--viniferin ,(-)-laevifonol, (-)-hopeaphenol , (-)-isohopeaphenol, vaticanol B, diptoindonesin E, hemsleyanol D, davidiol A, resveratrol, ampelopsin A, ampelopsin F, together with three other phenolic; gallic acid derivative, (-)-bergenin, scopoletin and 4-methoxygallocathecin and also two terpene; β-sitosterol and β-sitosterol glucoside have been isolated. In this study, the crude extracts and isolated compounds were evaluated regarding to their antifungal activity; in terms of MIC, MFC and germination assay against pathogenic fungi strains, namely Aspergillus flavus (AF), Aspergillus oligosporus (AO), Rhizophus oryzae (RO) and Fusarium oxysporum (FO) using Clinical and Laboratory Standard Institute (CLSI) methods. The MIC of crude extracts and isolated compounds against all fungi ranged from 3.8 - 500 μg/mL. F. oxysporum shows the most sensitive microorganisms on crude extract: D. verrucosus, D. cornutus and isolated compound: ε-viniferin with MIC of 3.8 μg/mL. The MIC was lower compared to amphotericin B (4 μg/ml). The strain was killed at the MFC of 31.3, 31.3 and 15.6 μg/mL respectively, as compared to amphotericin B (8 μg/mL). Compounds: resveratrol, laevifonol, ε-viniferin, ampelopsin F, vaticanol B, vaticanol A, isomer of hopeaphenol and isohopeaphenol, β-sitosterol and β-sitosterolglucoside possessed an inhibitory activity on the conidial germination of F. oxysporum at the concentration of 4× MIC. On top of that, D. cornutus, ampelopsin A and hemsleyanol D possessed a complete sterility at the concentration of 2×MIC while D.verrucosus achieved its inhibitory activity at 1× MIC. To the best of our study, there is no data discussing the inhibition of conidial germination of filamentous fungi using the tested compounds and crudes tested.